PS02.117: OUTCOMES FOR SQUAMOUS CELL CARCINOMA OF THE OESOPHAGUS IN A WESTERN POPULATION. (14th September 2018) - Madhavan, Anantha; Phillips, Alex; Wyatt, Nicola; Navidi, Maziar; Michael Griffin, S
Abstract: Background: Squamous cell carcinoma of the oesophagus comprises approximately 30% of oesophageal malignancies in the 'west'. Different approaches in management have been advocated. In the UK patients may receive conventional neoadjuvant chemotherapy (OEO2) or neoadjuvant chemoradiotherapy (CROSS). The aim of this study was to evaluate outcomes of patients receiving potentially curative surgical treatment for squamous cell carcinoma of the oesophagus. Methods: A retrospective review of patients who underwent treatment with curative intent for oesophageal squamous cell carcinoma between 2006 to 2016 at a single institution was performed. Patients underwent a standardised staging protocol and were assigned to the treatment modality based on the stage of the disease by a multi-disciplinary team. Outcomes were evaluated according to the treatment received. Results: Overall 199 patients underwent curative treatment in the 10 year period. This comprised 26% of the oesophagectomies for carcinoma. Of these, 168 patients had disease which was staged T3 and above or had evidence of nodal disease. 81% of these patients received neo-adjuvant treatment, 108 receiving chemotherapy alone and 29 receiving chemoradiotherapy. The remaining 31 patients underwent surgery alone. There was no significant difference in the clinical staging between the three treatment modalities, ( P = 0.25). There were 31 patients with early (T1/2 N0) cancer that underwent unimodality treatment in the form of surgery. Estimated median survival was 85 months for those that received chemotherapy and 53 months chemoradiotherapy ( P = 0.45). Within the surgical group those patients with locally advanced disease (T3 + or N + ) median survival was 19 months; median survival was not reached for early cancers. Conclusion: Both chemoradiotherapy and chemotherapy in the neoadjuvant setting combined with radical surgery enable excellent long-term outcomes to be achieved. Data from the Neo-aegis trial will hopefully inform which neoadjuvant treatment confers the greatest survival advantage. Disclosure: All authors have declared no conflicts of interest.